Evaluation of anxiolytic activity of compound Valeriana jatamansi Jones in mice - You Jie-Shu; Peng Min; Shi Jin-Li; Zheng Hu-Zhan; Liu Yong; Zhao Bao-Sheng; Guo Jian-You (BMC, 2012)
Abstract Background Compound Valeriana jatamansi Jones is a formula for treating anxiety-related diseases in the clinic, which is composed of Valeriana jatamansi Rhizoma et Radix, Ziziphi Spinosae Semen, Albiziae Cortex and Junci Medulla. The purpose of this study was to explore the anxiolytic properties of this compound in mice. Methods Male ICR mice were treated with compound Valerianae Jatamansi Jones (1.2 g/kg, 2.4 g/kg, 4.8 g/kg), saline, diazepam (2 mg/kg) orally for 10 days and then exposed to elevated maze-plus (EPM) and light-dark box (LDB). The effects of the compound on spontaneous activity were evaluated by locomotor activity test. We further investigated the mechanism of action underlying the anxiolytic-like effect of compound by pre-treating animals with antagonists of benzodiazepine (flumazenil, 3mg/kg) prior to evaluation using EPM and LDB. Results Compound Valerianae Jatamansi Jones (2.4, 4.8 g/kg, p.o.) significantly increased entries (P<0.05) into and time spent (P<0.05) on the open arms of the EPM, and number of transitions (P<0.05) and time spent (P<0.05) in the light compartment of the LDB. However, the anxiolytic-like effects of compound were significantly reduced by pre-treatment with flumazenil (P>0.05). In addition, compound Valerianae Jatamansi Jones treatment didn't affect the spontaneous activity in mice (P> 0.05). Conclusions The present study supports the hypothesis that compound Valeriana jatamansi Jones exert anxiolytic action but no sedative effects in mice and that this effect might be mediated by benzodiazepine receptors.